2022
DOI: 10.3389/fcvm.2022.961920
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human pilot trial of combined intracoronary and intravenous mesenchymal stem cell therapy in acute myocardial infarction

Abstract: BackgroundAcute ST-elevation myocardial infarction (STEMI) elicits a robust cardiomyocyte death and inflammatory responses despite timely revascularization.ObjectivesThis phase 1, open-label, single-arm, first-in-human study aimed to assess the safety and efficacy of combined intracoronary (IC) and intravenous (IV) transplantation of umbilical cord-derived mesenchymal stem cells (UMSC01) for heart repair in STEMI patients with impaired left ventricular ejection fraction (LVEF 30-49%) following successful reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Additionally, abundant evidence has clearly demonstrated that MSCs have the capacity to manage antioxidative stress, perform angiogenesis, and repair damaged tissue and organs, resulting in tissue/organ regeneration as well as improvement of mitochondrial dysfunction [ 25 , 26 , 27 , 29 , 30 ]. Additionally, even allogenic MSCs have been applied for patients with severe cardiovascular disease [ 31 ] or acute respiratory distress syndrome [ 32 ], and the results were reported to be safe and to have potentially improved the clinical outcomes. These findings [ 25 , 26 , 27 , 29 , 30 , 31 , 32 ] highlight that MSC therapy may possess therapeutic potential for NP patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, abundant evidence has clearly demonstrated that MSCs have the capacity to manage antioxidative stress, perform angiogenesis, and repair damaged tissue and organs, resulting in tissue/organ regeneration as well as improvement of mitochondrial dysfunction [ 25 , 26 , 27 , 29 , 30 ]. Additionally, even allogenic MSCs have been applied for patients with severe cardiovascular disease [ 31 ] or acute respiratory distress syndrome [ 32 ], and the results were reported to be safe and to have potentially improved the clinical outcomes. These findings [ 25 , 26 , 27 , 29 , 30 , 31 , 32 ] highlight that MSC therapy may possess therapeutic potential for NP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, even allogenic MSCs have been applied for patients with severe cardiovascular disease [ 31 ] or acute respiratory distress syndrome [ 32 ], and the results were reported to be safe and to have potentially improved the clinical outcomes. These findings [ 25 , 26 , 27 , 29 , 30 , 31 , 32 ] highlight that MSC therapy may possess therapeutic potential for NP patients. However, whether MSC therapy would provide benefits for NP is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study, Gong et al showed that a repeated intravenous dose of human umbilical cord-derived MSCs had a superior therapeutic effect than single-dose treatment in improving the LV function of rats with dilated cardiomyopathy (33). In a groundbreaking phase 1 trial, Hsiao et al found that combined intracoronary and intravenous (two days apart) umbilical cord-derived MSCs appeared to be safe, feasible, and effective (9.80 ± 7.56% rise in EF after 12 months), though con rmatory phase 2 studies are needed (34). On the other hand, we delivered the stem cells via an intracoronary microinfusion, which a meta-analysis revealed to have similar e cacy as a transendocardial injection (23).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al reported that, three months after the first transfer in patients with large MI, repeated bone marrow mononuclear cell infusion through the IC route could improve cardiac function [22]. Hsiao et al showed a reduction of myocardial damage in patients by combining IC and IV administration [23].…”
Section: Cell Therapymentioning
confidence: 99%
“…Although the application of melt electrospun scaffolds for engineering is improper for cell encapsulation purposes, foldable PCL melt electrospun hexagonal-shaped scaffolds (8 mm diameter, 300 µm thick) promoted the CM alignment and maturation [51]. Some practical limitations in using electrospinning are the possible toxic effect of remaining chemical ingredients during the electrospinning postprocessing [22], an insufficient mechanical force for load-bearing aims [23], poor cell infiltration and migration of the cells [22,24,52], and the insufficient biochemical complexity of the cardiac ECM [53].…”
Section: Electrospinningmentioning
confidence: 99%